Social Conflict Between Government and Communities in Medan City (Case Study of Residents Evictions in Medan Estate - Herti Noita Simbolon; Cindy Ayu Lestari; Lehonna Yo Gracia Simanjuntak; Siti Anisah Nasution; Sadnes Sinaga; Julia Ivanna (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted in Medan Estate with informan as many as two people, community evictees homes affected land evictions. The result found is the community objected to the government’s evictions. They said that they had rented the land and had the right to ocuppy it. However, the government still insist on evicting the house and businesses in it, having previously warned the government to move from thr land immediately. The method used in this research is qualitative research method are closely related to the social definition paradigm.